Overview on postmenopausal osteoporosis and periodontitis: The therapeutic potential of phytoestrogens against alveolar bone loss - Jayusman, Putri Ayu; Nasruddin, Nurrul Shaqinah; Baharin, Badiah; Ibrahim, Nurul ‘Izzah; Ahmad Hairi, Haryati; Shuid, Ahmad Nazrun (Frontiers in Pharmacology, 2023)
Osteoporosis and periodontitis are two major chronic diseases of postmenopausal women. The association between these two diseases are evident through systemic bone loss and alveolar bone loss. Both postmenopausal osteoporosis and periodontitis impose a considerable personal and socioeconomic burden. Biphosphonate and hormone replacement therapy are effective in preventing bone loss in postmenopausal osteoporosis and periodontitis, but they are coupled with severe adverse effects. Phytoestrogens are plant-based estrogen-like compounds, which have been used for the treatment of menopause-related symptoms. In the last decades, numerous preclinical and clinical studies have been carried out to evaluate the therapeutic effects of phytoestrogens including bone health. The aim of this article is to give an overview of the bidirectional interrelationship between postmenopausal osteoporosis and periodontitis, summarize the skeletal effects of phytoestrogens and report the most studied phytoestrogens with promising alveolar bone protective effect in postmenopausal osteoporosis model, with and without experimental periodontitis. To date, there are limited studies on the effects of phytoestrogens on alveolar bone in postmenopausal osteoporosis. Phytoestrogens may have exerted their bone protective effect by inhibiting bone resorption and enhancing bone formation. With the reported findings on the protective effects of phytoestrogens on bone, well-designed trials are needed to better investigate their therapeutic effects. The compilation of outcomes presented in this review may provide an overview of the recent research findings in this field and direct further in vivo and clinical studies in the future.